PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KETAHANAN PANGAN DAN PELAKSANA PENYULUHAN DAERAH KOTA SAMARINDA - Mukti Ali (Jurnal Paradigma (JP), 2017)
Work satisfaction can increase the employee achievement, it can produce high motivation for the employee to contribute significantly to his organization. In order to show work satisfaction in the organization it needs the support from the all members of oragnization. Meanwhile at the same time to achieve the good performance of Samarinda agriculture department  considered by several factors; opportunity, compensation, work partner, and leadership.